لفظ القسم ومرادفاته في السور المدنية - Fitri Annisa Hayati (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2018)
This research is meant to describe : (i) Various synonyms of the word oath in Madani surahs (2) The importance or the usage of the word oath and  its synonyms in Madani surahs (3) The contexts of the word oath and its synonyms in Madani surahs. The research methodology used is qualitative descriptive. The results of the research are as follows : (1) There are 7 words as synonyms of the word oath in Madaniah surahs. They are aqsama and yuqsimu, halafa and yahlifuna, special oath fala warabbika, nabtahil, yu'luna and ya'tali, syahadatin billahi and aiman. (2) In Madani  surahs, the researcher finds that there are four function of the word oath and their synonyms, namely to throw away doubt, to strengthen the reason, to strengthen the statement and to define the law perfectly. (3) The contexts used to distinguish the word oath and its synonyms are linguistic and non-linguistic (situation) contexts